Response to the growth of tomato plant (Solanum lycopersicum L.) to giving variation of organic fertilizers - Meiliana, Friska; Jumaria, Nasution (Talenta Publisher, 2020)
Tomato plant (Solanum Lycopersicum L.) is one of the horticultural commodities that have the potential to be developed because it has quite high economic value. One of the efforts made to increase the growth of tomato plants is by using organic fertilizers. Organic fertilizer is the best and natural soil repairer than artificial/synthetic. This study aims to determine the response of tomato plant growth to organic fertilizer by observing plant height, the number of leaves, and stem diameter. This study used an experimental method with a randomized block design consisting of 4 treatments, namely compost, manure, and green manure. The results of the observations were analyzed using Analysis of Variance (ANOVA) and statistical data processing was performed using the F test at the level of Î± = 5%. The results showed that the growth of tomato plants for the highest plant measurement, the highest average number of leaves, and stem diameter were found in the compost (PK) treatment.